Calculation of the Relaxation Time and the Activation Energy Close to the Lower Phase Transition in Imidazolium Perchlorate - Yurtseven, Hamit; A. Kiraci; N. Kara (Journal of Basic & Applied Sciences, 2021)
The temperature dependence of the relaxation time of imidazolium perchlorate (Im-ClO4) was calculated from the pseudospin-phonon coupled (PS) and the energy fluctuation (EF) models close to the first-order phase transition temperature of 247 K. This calculation was performed in terms of the proton second moment M2 that was associated with the order parameter which was predicted from the mean-field theory. Our results were in good agreement with the observed data. In addition, values of the activation energy were deduced in terms of the Arrhenius plot using our calculated values of the relaxation time from both PS and EF models.